(untitled) (The All Results Journal, 2012)
Sulfonamides are usual ligands for organometallic catalysis in the Ring Opening Polymerization (ROP) of cyclic esters. In our quest for original Hydrogen-bonding catalytic systems, our goal was to use a sulfonamide derivative as an electrophilic activator of DL-lactide in partnership with a tertiary amine, as a nucleophilic activator of the initiator and growing polymer chain. Several sulfonamides were synthesized and tested in the ROP of DL-lactide. The impact of sulfonamide substituents was analyzed to better understand the H-bonds involved in the process.